Protease e farinha de penas na alimentação de frangos de corte - Christiane Fernanda de Queiroz Matias (2016)
The purpose of this research is to evaluate the effects of protease use (produced by Bacillus licheniformis strain PWD-1) and its nutritional contribution in broiler chicken feed containing or not poultry-feather meal (PFM) on metabolization coefficient of nutrients, performance, slaughter yield and enzymatic production. Four experiments were conducted in a completely randomized design, using four treatments with six replicates each. In experiment 1, PFM was added to all diets. In the initial phase the design used was a 2x2 factorial arrangement (with or without protease inclusion X considering or not nutrient improvement value from the enzyme), while in the growth phase a completely randomized design was used. It was observed on the 14th day of age, the birds that consumed feed with enzyme, regardless of the nutritional improvement value, presented lower values (P≤0.05) of total protein concentration, pancreatic trypsin and chymotrypsin. In the growth phase, there was a higher body weight gain (BWG) for the treatment enzyme added in which nutritional contribution of the enzyme was not considered (added on top). In experiment II, poultry-feather meal was not added to any diets and its design was in a 2x2 factorial arrangement (with or without protease inclusion X considering or not nutrient improvement value from the enzyme) at initial and growth phases. Broilers fed diets without considering nutrient improvement values from enzyme (P≤0,05), in initial phase, presented better feed conversion (FC) (P≤0,05), in spite of enzyme addition. Body weight gain (BWG) at both phases was superior for birds fed diets without considering nutrient improvement values from enzyme (P≤0,05), regardless of enzyme inclusion. In experiment III, the protease was included in all diets and the design was in a 2x2 factorial arrangement (with or without PFM inclusion X considering or not nutrient improvement value from the enzyme). Diets formulated considering enzyme nutritional enhancement resulted in higher MCDM e MCCP (P≤0,05) throughout initial phase, whether or not PFM was added. Feed diets without PFM inclusion and feed diets with addition of enzyme on top resulted in higher BWG (P≤0,05). Throughout initial phase, best results of FC were observed in birds fed diets with PFM (P≤0,05), regardless of whether enzyme nutrient sparing effect were accounted or not. In experiment IV, the design used was a 2x2 factorial arrangement (with or without protease inclusion X two nutrients improvement value from the enzyme) and PFM were included in all diets. None of the variables were influenced by the treatments. As a general conclusion, in none of the experiments performed, the viability, carcass and cuts yields were not affected by any treatment in all experiments (P≤0,05). MCCP e MCEE best results were shown when diets were formulated considering enzyme nutritional contribution. Enzyme added on top, without considering its nutritional value, improved BWG, with no effect on cuts yields. The recommended nutrient sparing effect of the protease appears to be excessive for commercial diets of broiler chickens.